PENINGKATAN KEMAMPUAN MENULIS TEKS PIDATO MELALUI MODEL PROJECT BASED LEARNING (PJBL) PADA SISWA KELAS VIII D SMPN 14 DENPASAR - Elva Arini Mardatillah; I GAP Tuti Indrawati; Ni Luh Gede Nofa Debiliastini (Jurnal Manajemen Pendidikan, 2026)
This study aims to: (1) describe the implementation of the Project Based Learning (PjBL) model in teaching speech text writing to students of class VIII D at SMPN 14 Denpasar, (2) improve students’ speech text writing skills through the implementation of the Project Based Learning (PjBL) model, and (3) enhance students’ learning activities during the learning process. This study employed Classroom Action Research (CAR) consisting of four stages: planning, action, observation, and reflection. The subjects of the study were 40 students of class VIII D at SMPN 14 Denpasar in the 2025/2026 academic year. The research was conducted in two cycles, using observation, interviews, tests, and documentation as data collection techniques. The data were analyzed using descriptive quantitative and qualitative methods to determine the improvement in students’ speech text writing skills and learning activities. The results showed that the implementation of the Project Based Learning (PjBL) model improved students’ speech text writing skills and learning activities. The improvement in speech text writing skills was indicated by the increase in the students’ mean score from 68.13 in the pre-cycle to 77.75 in Cycle I and further increased to 87.25 in Cycle II. Students’ learning mastery also improved, from 30.00% in the pre-cycle to 62.50% in Cycle I and reached 92.50% in Cycle II. Students’ learning activities increased from 73.75% in Cycle I, categorized as good, to 90.63% in Cycle II, categorized as very good.